2020
DOI: 10.1007/s10926-020-09879-x
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Workplace Interventions to Rehabilitate Musculoskeletal Disorders Among Employees with Physical Demanding Work

Abstract: Purpose This systematic review investigates the effectiveness of workplace interventions to rehabilitate musculoskeletal disorders (MSDs) among employees with physically demanding work. Methods A systematic search was conducted in bibliographic databases including PubMed and Web of Science Core Collection for English articles published from 1998 to 2018. The PICO strategy guided the assessment of study relevance and the bibliographical search for randomized controlled trials (RCTs) and non-RCTs in which (1) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
94
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(116 citation statements)
references
References 91 publications
2
94
0
1
Order By: Relevance
“…The qualitative feedback from this study provides some valuable insight into workplace stretching programs. Participants in this study reported positive effects on physical health as previously reported in the literature 5,10 but they also described unanticipated benefits of the program on their psychological wellbeing and the overall workplace culture. These findings suggest that the mechanism of action of workplace stretching programs may be more complicated than first thought.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The qualitative feedback from this study provides some valuable insight into workplace stretching programs. Participants in this study reported positive effects on physical health as previously reported in the literature 5,10 but they also described unanticipated benefits of the program on their psychological wellbeing and the overall workplace culture. These findings suggest that the mechanism of action of workplace stretching programs may be more complicated than first thought.…”
Section: Discussionsupporting
confidence: 71%
“…Benefits of stretching include improved flexibility, range of motion, circulation, posture and stress relief 4 . Workplace stretching has been shown to reduce musculoskeletal discomfort and injury in office workers, factory workers and firefighters 5 . There has been recent evidence of the benefit of workplace stretching programs for surgeons [6][7][8] but not for other perioperative staff.…”
Section: Introductionmentioning
confidence: 99%
“…A study on nurses working in general wards showed a reduction in musculoskeletal pain in the areas of the neck, shoulder and knee after the implementation of an ergonomic educational intervention [ 17 ]. However, some studies have reported no significant benefit or the limited success of ergonomics interventions on MSDs [ 18 , 19 ], which can be attributed to variations in their educational interventions, samples and settings, data collection tools, and the research structure. Therefore, more studies should be carried out to develop conclusive evidence on the effectiveness of ergonomics educational interventions in the reduction of MSDs among clinical nurses.…”
Section: Introductionmentioning
confidence: 99%
“…12 13 Therefore, clinical practice guidelines have focused on the importance of returning to normal activities as the most optimal strategy of recovery from chronic pain conditions. 14 Emerging evidence also stresses the importance of return to work (RTW) as one of the main goals of treatment, [15][16][17][18][19] since RTW can be regarded as an indicator of better health status and recovery. 20 Hence, RTW is a core outcome, not only for society but also for chronic pain sufferers themselves.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated above, the loss of productivity due to CNMP is enormous, 5 6 and thus it is essential to implement cost-effective interventions to facilitate RTW. [15][16][17][18][19] Moreover, work presenteeism is associated with an array of physical and mental health benefits, 21 22 whereas work absenteeism is associated with an array of unfavourable physical and mental health outcomes, leading to a worse financial situation. [23][24][25] Currently, the benefits of RTW interventions remain uncertain.…”
Section: Introductionmentioning
confidence: 99%